MELATIH ADAPTASI KEBIASAAN BARU PADA ANAK - Ningrum, Nyna Puspita (Seminar Nasional Pengabdian Kepada Masyarakat UNDIP 2020; Prosiding Seminar Nasional Pengabdian Masyarakat UNDIP 2020, 2020)
Community Service Activities (PPM) with the theme "Practicing Adaptation of New Habits in Children" were carried out online by adjusting to conditions in the midst of a pandemic. This activity is an effort of the Faculty of Health Sciences to assist and support the Government in increasing public knowledge in entering the New Habit Adaptation period. The purpose of this PPM is to provide information on how to train children in preparing children to behave, according to health protocols, so that children are responsive and care about their health. The role of the family is very important for survival during the process of adapting to new habits. According to data from the Indonesian Pediatrician Association (IDAI), the number of children with the status of patients under surveillance (PDP) was 3400 children, PDP deaths were 129 children, positive Covid-19 in children was 584 cases, and 14 child deaths from positive cases of Covid-19. The high incidence of Covid-19 transmission in children proves that it is not true that the age group of children is not susceptible to Covid-19, so the government and society must be vigilant in maintaining children's health and welfare. Through the role of the family, it is hoped that they will be able to train children in accordance with health protocols in preventing transmission of the Corona virus, so that they can improve children's health during the adaptation period of new habits. It is hoped that the virtual family role webinars will add insight and improve the health of families, especially children. Thus, family health resilience in facing the adaptation period for new habits can be achieved.